Self-assembled 3D heterometallic Zn(II)/K(I) metal–organic framework with the fluorite topology. (1st March 2018) - Abedi, Marjan; Mahmoudi, Ghodrat; Kirillov, Alexander M.; Kaminsky, Werner
Graphical abstract: Self-assembly generation and structural features of a novel heterometallic Zn(II)/K(I) metal–organic framework have been investigated. Abstract: Treatment of zinc(II) acetate with a ditopic (bis-tridentate) thiocarbazone {H2 L, bis(pyridine-2-aldehyde) thiocarbazone} as a principal building block and potassium thiocyanate as a source of auxiliary ligand resulted in the self-assembly generation of a novel heterometallic Zn(II)/K(I) metal–organic framework (MOF) formulated as [Zn2 (L)K2 (µ2 -H2 O)2 (µ2 -SCN)4 ] n (1 ). It was isolated as a microcrystalline solid and fully characterized, including by single crystal X-ray diffraction. Crystal structure of1 reveals a very intricate 3D framework assembled from the [Zn2 L] 2+ and [K2 (µ2 -H2 O)2 ] 2+ secondary building units (SBUs) and multiple µ2 -thiocyanate linkers. Topological analysis of the simplified underlying net of1 disclosed a binodal 4, 8-connected framework with theflu (fluorite) topology. Synthesis, characterization, structural and topological features, as well as Hirshfeld surface analysis are discussed in the present study.